Thymol nanoemulsion promoted broiler chicken’s growth, gastrointestinal barrier and bacterial community and conferred protection against Salmonella Typhimurium - Doaa Ibrahim (Nature Portfolio, 2021)
Abstract The present study involved in vivo evaluation of the growth promoting effects of thymol and thymol nanoemulsion and their protection against Salmonella Typhimurium infection in broilers. One-day old 2400 chicks were randomly divided into eight groups; negative and positive control groups fed basal diet without additives and thymol and thymol nanoemulsion groups (0.25, 0.5 and 1% each). At d 23, all chicks except negative control were challenged with S. Typhimurium. Over the total growing period, birds fed 1% thymol nanoemulsion showed better growth performance even after S. Typhimurium challenge, which came parallel with upregulation of digestive enzyme genes (AMY2A, PNLIP and CCK). Additionally, higher levels of thymol nanoemulsion upregulated the expression of MUC-2, FABP2, IL-10, IgA and tight junction proteins genes and downregulated IL-2 and IL-6 genes expression. Moreover, 1% thymol nanoemulsion, and to lesser extent 0.5% thymol nanoemulsion and 1% thymol, corrected the histological alterations of cecum and liver postinfection. Finally, supplementation of 1% thymol, 0.5 and 1% thymol nanoemulsion led to increased Lactobacilli counts and decreased S. Typhimurium populations and downregulated invA gene expression postinfection. This first report of supplying thymol nanoemulsion in broiler diets proved that 1% nano-thymol is a potential growth promoting and antibacterial agent.